2011
DOI: 10.1212/wnl.0b013e318207b031
|View full text |Cite
|
Sign up to set email alerts
|

Phase I trial of pegylated interferon-α-2b in young patients with plexiform neurofibromas

Abstract: Objective: Interferon has antiproliferative and antiangiogenic properties. We sought to evaluate preliminary efficacy and determine the recommended phase II dose (RP2D) for pegylated interferon-␣-2b (PI) in patients with unresectable progressive or symptomatic plexiform neurofibromas (PN).Methods: PI was administered weekly in cohorts of 3-6 patients during the dose-finding phase and continued for up to 2 years. Twelve patients were treated at the RP2D to further evaluate toxicity and activity.Results: Thirty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 21 publications
1
22
0
1
Order By: Relevance
“…25 Behavioral issues, including attention-deficit hyperactivity disorder, are commonly seen in patients with NF1 26 and worsening of such and/or fatigue were dose-limiting toxicities in the phase I study. 17 Similarly, treatment-limiting behavioral issues and/or fatigue occurred in 12% and 14% of patients, respectively, in the current study; the majority of behavioral issues were preexisting and worsened on therapy. Four of the 14 patients (28.6%) enrolled in the pain stratum either came off study or required a dose reduction for mood/behavioral issues, most of which were preexisting, Fig.…”
Section: Neurooncologysupporting
confidence: 63%
See 1 more Smart Citation
“…25 Behavioral issues, including attention-deficit hyperactivity disorder, are commonly seen in patients with NF1 26 and worsening of such and/or fatigue were dose-limiting toxicities in the phase I study. 17 Similarly, treatment-limiting behavioral issues and/or fatigue occurred in 12% and 14% of patients, respectively, in the current study; the majority of behavioral issues were preexisting and worsened on therapy. Four of the 14 patients (28.6%) enrolled in the pain stratum either came off study or required a dose reduction for mood/behavioral issues, most of which were preexisting, Fig.…”
Section: Neurooncologysupporting
confidence: 63%
“…A phase I study of PI in pediatric patients with unresectable PN showed both clinical and imaging responses by volumetric MRI analysis and established the recommended phase II dose of 1.0 mcg/kg/wk given by subcutaneous injection. 17 We therefore undertook a phase II trial evaluating the imaging (stratum 1) and/or clinical (stratum 2) response rates in patients with unresectable PN. Stratum 3 evaluated the impact of PI on growth rate in patients with documented progression on imaging at trial entry by comparing time to progression (TTP) with the actuarial curve of the placebo arm of the National Cancer Institute-coordinated tipifarnib trial (NCT00021541).…”
mentioning
confidence: 99%
“…Therefore, more sensitive methods, such as volume segmentation, were developed for the analysis of PN and schwannomas. [10][11][12][13][14][15] These methods documented the feasibility of reproducibly measuring tumor volumes in natural history studies and treatment trials for PN and VS. 13,14,[16][17][18][19] Using the MEDx-based lesion detection method developed for PN, interobserver differences were less than 10% and intraobserver variation was #5%. 10 For VS measured using the Vitrea2 workstation, the coefficient of variation ranged from 0.6% to 6.8%.…”
Section: Standard Criteria For Response Evaluation In Clinical Trialsmentioning
confidence: 99%
“…12 In children, a normal AHI is ,1.5. In adults, a normal AHI is ,5; the degree of OSA can be classified as mild , moderate (AHI [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], or severe (AHI .30). Treatment of OSA is directed at maintaining patency of the upper airway.…”
mentioning
confidence: 99%
“…In recent years, shrinkage of PNs has been observed after treatment with PEG-intron, imatinib, and selumetinib. [15][16][17] Because clinical benefit may occur with minimal volume changes, sleep and pulmonary outcomes may be more sensitive than radiographic changes at detecting a meaningful response to treatment. Our objectives were to define reproducible and clinically meaningful measures of sleep and pulmonary function, which can be used as primary endpoints in clinical trials targeting airway PNs.…”
mentioning
confidence: 99%